Factors Related to the Risk of Musculoskeletal Disorders in Welding Workshop Workers in Lhokseumawe City in 2019 - Diana Putri; Gerry Silaban; Ikhwansyah Isranuri (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Working in an awkward posture without using work aids for welding shop workers can pose a risk of Musculoskeletal Disorders. The study aims to determine the factors associated with the risk of Musculoskeletal Disorders in welding workshop workers in the city of Lhokseumawe. This type of research is a type of quantitative research, with a cross sectional approach. Performed on 40 populations which are all used as samples. Data collection was carried out through interviews using the Nordic Body Map (NBM) worksheet to determine the level of MSDs complaints and to find out whether age, education, years of work, number of hours worked, number of hours of rest (independent variables) affected the MSDs (dependent variable). The results showed that there was an influence of the age factor (p value = 0,000), years of service (p value = 0,000), the number of hours worked (p value = 0.009) and the number of hours of sleep (p value = 0.009) on the risk of MSDs, but the education factor did not show the effect which is significant (pvalue = 0.548). The conclusions of this study are: age, years of work, number of hours worked and number of hours of sleep are the causes of MSDs risk in welding workshop workers except the level of education which is mostly high school. It is recommended to welding workshop workers to use tools such as work desks to reduce the odd work posture, the allocation of working time in accordance with the applicable government regulations, namely 7 hours a day by business owners, as well as the continuity of activities of the UKK Team towards informal workers both in terms of knowledge transfer (counseling) and health services.